Book Review “Political Ecology: A Critical Introduction, 2nd Edition” by Paul Robbins - Madalina Epure (Journal of Economic Development, Environment and People, 2015)
Book Review “Political Ecology: A Critical Introduction, 2nd Edition” by Paul Robbins